IMPLEMENTASI PEMBELAJARAN SENI MUSIK TRADISIONAL DALAM MENUMBUHKAN LITERASI BUDAYA SISWA SEKOLAH DASAR - Nala Kania; -, Anisa Putri Mulyaningsih; -, Ferdhina Salzabila Septiani; -, Mila Marliana; -, Teten Ginanjar Rahayu (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2026)
This research aims to analyze the implementation of traditional music arts learning in fostering the cultural literacy of elementary school students. The method used was Systematic Literature Review (SLR) with PRISMA guidelines for 60 articles from the Google Scholar database, resulting in 9 relevant articles. The results of the study show that traditional music learning in elementary schools is implemented through various innovations such as digital media, Augmented Reality (AR), educational videos, social media, and thematic learning models based on local culture. This learning not only focuses on artistic skills, but also plays a role in increasing cultural understanding, building cultural identity and pride, and fostering student creativity, participation and character. Apart from that, learning traditional music also contributes to preserving culture amidst globalization. However, its implementation still faces obstacles such as limited teacher competence, lack of learning facilities, and low student interest. Overall, traditional music learning has proven to be effective and relevant in increasing the cultural literacy of elementary school students through an innovative and contextual approach.